2009
DOI: 10.1111/j.1524-4741.2009.00833.x
|View full text |Cite
|
Sign up to set email alerts
|

The Yale University Experience of Early-Stage Invasive Lobular Carcinoma (ILC) and Invasive Ductal Carcinoma (IDC) Treated with Breast Conservation Treatment (BCT): Analysis of Clinical-Pathologic Features, Long-Term Outcomes, and Molecular Expression of COX-2, Bcl-2, and p53 as a Function of Histology

Abstract: To evaluate our experience of the clinical-pathologic features and outcomes of early-stage Invasive Lobular (ILC) versus Invasive Ductal (IDC) carcinoma treated with breast conservation treatment (BCT). 142 ILC and 1,760 IDC patients were treated with BCT at our institution. All patients underwent breast conserving surgery and radiation therapy (median total dose: 64 Gy). Clinical-pathologic and outcome parameters were analyzed to detect differences between the two cohorts. In addition, COX-2, Bcl-2, and p-53 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 31 publications
3
20
1
3
Order By: Relevance
“…It should be noted that in the Pestalozzi et al [12] study of 767 ILC cases, an early advantage in DFS (16% lower event incidence) was observed for the ILC patients, followed by a late advantage for IDC patients after 6 years (54% higher incidence of events for ILC patients). Similar results for OS have been documented, with the majority of studies revealing no difference between the groups at 5 and 10 years [6,7,8,15,21,22,25]. Cristofanilli et al [7] found improved OS for ILC patients at 70 months, while Pestalozzi et al [12] found that ILC patients had an early advantage in OS (16% lower risk of death) but that IDC patients again had a late advantage after 10 years (50% higher risk of death for ILC patients).…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…It should be noted that in the Pestalozzi et al [12] study of 767 ILC cases, an early advantage in DFS (16% lower event incidence) was observed for the ILC patients, followed by a late advantage for IDC patients after 6 years (54% higher incidence of events for ILC patients). Similar results for OS have been documented, with the majority of studies revealing no difference between the groups at 5 and 10 years [6,7,8,15,21,22,25]. Cristofanilli et al [7] found improved OS for ILC patients at 70 months, while Pestalozzi et al [12] found that ILC patients had an early advantage in OS (16% lower risk of death) but that IDC patients again had a late advantage after 10 years (50% higher risk of death for ILC patients).…”
Section: Discussionsupporting
confidence: 60%
“…Cristofanilli et al [7] found improved OS for ILC patients at 70 months, while Pestalozzi et al [12] found that ILC patients had an early advantage in OS (16% lower risk of death) but that IDC patients again had a late advantage after 10 years (50% higher risk of death for ILC patients). Previous studies of DSS have found a higher incidence of breast cancer mortality for ILC patients at >10 years, with mixed survival data at earlier time points [6,9,15,25]. In our subgroup analysis, a substantial disadvantage in OS was observed for stage IV ILC patients compared to stage IV IDC patients, with a mean OS of 2.9 versus 6.8 years.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations